Nas malhas do discurso: a mulher empresária na revista de colunismo social Deluxe - VALE, Letícia Maciel do (2020)
This research work proposes to understand the discursive strategies that are manifested in the constitution of the subject woman shown as a successful businesswoman by Deluxe magazine, a social columnism segment’s vehicle that integrates the media apparatus. The research uses the theoretical principles of Discourse Analysis of the French line, based on Michel Foucault’s reflections and the archenegenealogical method, which seeks to understand the relations of knowledge, power and truth that present in the production of discourses. We also consider the discussions about governmentality, biopower and biopolitics, to understand the processes of normalization and disciplinarity to which the body of the discursivized woman as a successful businesswoman is subjected. Thus, we verified that there are rules that control and discipline this subject's body, making it economically useful and politically docile, and that they are related to topics such as beauty / health, motherhood / family, studies, work and charity / faith / care with each other. The magazine builds an objectification, a way of looking and saying about the body of a successful businesswoman, in which statements dispersed in history appear intertwined in a discursive formation that shows this subject as a model to be followed. The subject, in turn, builds subjectivity and recognizes himself in the discourse that the magazine produces about her.